Answer:
<h3>For two events A and B show that P (A∩B) ≥ P (A)+P (B)−1.</h3>
By De morgan's law
![(A\cap B)^{c}=A^{c}\cup B^{c}\\\\P((A\cap B)^{c})=P(A^{c}\cup B^{c})\leq P(A^{c})+P(B^{c}) \\\\1-P(A\cap B)\leq P(A^{c})+P(B^{c}) \\\\1-P(A\cap B)\leq 1-P(A)+1-P(B)\\\\-P(A\cap B)\leq 1-P(A)-P(B)\\\\P(A\cap B)\geq P(A)+P(B)-1](https://tex.z-dn.net/?f=%28A%5Ccap%20B%29%5E%7Bc%7D%3DA%5E%7Bc%7D%5Ccup%20B%5E%7Bc%7D%5C%5C%5C%5CP%28%28A%5Ccap%20B%29%5E%7Bc%7D%29%3DP%28A%5E%7Bc%7D%5Ccup%20B%5E%7Bc%7D%29%5Cleq%20P%28A%5E%7Bc%7D%29%2BP%28B%5E%7Bc%7D%29%20%5C%5C%5C%5C1-P%28A%5Ccap%20B%29%5Cleq%20%20P%28A%5E%7Bc%7D%29%2BP%28B%5E%7Bc%7D%29%20%5C%5C%5C%5C1-P%28A%5Ccap%20B%29%5Cleq%20%201-P%28A%29%2B1-P%28B%29%5C%5C%5C%5C-P%28A%5Ccap%20B%29%5Cleq%20%201-P%28A%29-P%28B%29%5C%5C%5C%5CP%28A%5Ccap%20B%29%5Cgeq%20P%28A%29%2BP%28B%29-1)
which is Bonferroni’s inequality
<h3>Result 1: P (Ac) = 1 − P(A)</h3>
Proof
If S is universal set then
![A\cup A^{c}=S\\\\P(A\cup A^{c})=P(S)\\\\P(A)+P(A^{c})=1\\\\P(A^{c})=1-P(A)](https://tex.z-dn.net/?f=A%5Ccup%20A%5E%7Bc%7D%3DS%5C%5C%5C%5CP%28A%5Ccup%20A%5E%7Bc%7D%29%3DP%28S%29%5C%5C%5C%5CP%28A%29%2BP%28A%5E%7Bc%7D%29%3D1%5C%5C%5C%5CP%28A%5E%7Bc%7D%29%3D1-P%28A%29)
<h3>Result 2 : For any two events A and B, P (A∪B) = P (A)+P (B)−P (A∩B) and P(A) ≥ P(B)</h3>
Proof:
If S is a universal set then:
![A\cup(B\cap A^{c})=(A\cup B) \cap (A\cup A^{c})\\=(A\cup B) \cap S\\A\cup(B\cap A^{c})=(A\cup B)](https://tex.z-dn.net/?f=A%5Ccup%28B%5Ccap%20A%5E%7Bc%7D%29%3D%28A%5Ccup%20B%29%20%5Ccap%20%28A%5Ccup%20A%5E%7Bc%7D%29%5C%5C%3D%28A%5Ccup%20B%29%20%5Ccap%20S%5C%5CA%5Ccup%28B%5Ccap%20A%5E%7Bc%7D%29%3D%28A%5Ccup%20B%29)
Which show A∪B can be expressed as union of two disjoint sets.
If A and (B∩Ac) are two disjoint sets then
B can be expressed as:
![B=B\cap(A\cup A^{c})\\](https://tex.z-dn.net/?f=B%3DB%5Ccap%28A%5Ccup%20A%5E%7Bc%7D%29%5C%5C)
If B is intersection of two disjoint sets then
![P(B)=P(B\cap(A)+P(B\cup A^{c})\\P(B\cup A^{c}=P(B)-P(B\cap A)](https://tex.z-dn.net/?f=P%28B%29%3DP%28B%5Ccap%28A%29%2BP%28B%5Ccup%20A%5E%7Bc%7D%29%5C%5CP%28B%5Ccup%20A%5E%7Bc%7D%3DP%28B%29-P%28B%5Ccap%20A%29)
Then (1) becomes
![P(A\cup B) =P(A) +P(B)-P(A\cap B)\\](https://tex.z-dn.net/?f=P%28A%5Ccup%20B%29%20%3DP%28A%29%20%2BP%28B%29-P%28A%5Ccap%20B%29%5C%5C)
<h3>Result 3: For any two events A and B, P(A) = P(A ∩ B) + P (A ∩ Bc)</h3>
Proof:
If A and B are two disjoint sets then
![A=A\cap(B\cup B^{c})\\A=(A\cap B) \cup (A\cap B^{c})\\P(A)=P(A\cap B) + P(A\cap B^{c})\\](https://tex.z-dn.net/?f=A%3DA%5Ccap%28B%5Ccup%20B%5E%7Bc%7D%29%5C%5CA%3D%28A%5Ccap%20B%29%20%5Ccup%20%28A%5Ccap%20B%5E%7Bc%7D%29%5C%5CP%28A%29%3DP%28A%5Ccap%20B%29%20%2B%20P%28A%5Ccap%20B%5E%7Bc%7D%29%5C%5C)
<h3>Result 4: If B ⊂ A, then A∩B = B. Therefore P (A)−P (B) = P (A ∩ Bc) </h3>
Proof:
If B is subset of A then all elements of B lie in A so A ∩ B =B
where A and A ∩ Bc are disjoint.
![P(A)=P(B\cup ( A\cap B^{c}))\\\\P(A)=P(B)+P( A\cap B^{c})](https://tex.z-dn.net/?f=P%28A%29%3DP%28B%5Ccup%20%28%20A%5Ccap%20B%5E%7Bc%7D%29%29%5C%5C%5C%5CP%28A%29%3DP%28B%29%2BP%28%20A%5Ccap%20B%5E%7Bc%7D%29)
From axiom P(E)≥0
![P( A\cap B^{c})\geq 0\\\\P(A)-P(B)=P( A\cap B^{c})\\P(A)=P(B)+P(A\cap B^{c})\geq P(B)](https://tex.z-dn.net/?f=P%28%20A%5Ccap%20B%5E%7Bc%7D%29%5Cgeq%200%5C%5C%5C%5CP%28A%29-P%28B%29%3DP%28%20A%5Ccap%20B%5E%7Bc%7D%29%5C%5CP%28A%29%3DP%28B%29%2BP%28A%5Ccap%20B%5E%7Bc%7D%29%5Cgeq%20P%28B%29)
Therefore,
P(A)≥P(B)
Answer:
k = 7/6
Step-by-step explanation:
Answer:
Blank 1: 64° (or 32°, depending on what the label applies to)
Blank 2: 42
Step-by-step explanation:
It is a common mistake to believe you have solved the problem when you have found the value of the variable(s) in the problem. You have correctly found the values of n (42) and m (9). However, that is not what the problem is asking for.
We cannot tell if the value (1/2n+11)° is referring to angle DAB, or to angle CAB. In any event, (1/2n+11)° = (1/2×42 +11)° = 32°.
If that is angle CAB, then angle DAB is twice that value, 64°.
If that is angle DAB, then angle DAB is 32°.
__
The side length CD is the same as any other side length in a rhombus, so ...
CD = 4m+6 = 4×9 +6
CD = 42 . . . . units
Answer:
y = 2x
linear equations are just finding the right ratio and putting it in y = mx+b format
this graph is saying that two dollars are earned for every ticket sold, a 2:1 ratio.
so the equation would be y = 2x, two being the amount of money collected for one ticket, and x being the number of tickets sold.